1991
DOI: 10.1055/s-2008-1042449
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Spina Bifida Children with and without Upper Renal Tract Changes at Birth

Abstract: The aim of this study was to assess 2 groups of children with spina bifida; one with and the other without upper renal tract (URT) changes at birth and to evaluate the outcome of their management. In Group 1, there were 148 patients who had normal URT at birth. They were studied for a mean follow-up of 131 months. Twenty-eight per cent developed URT changes in later life. The median time interval for URT changes to develop between birth and the first assessment which showed abnormal finding, was 33 months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Early start of CIC is the most important factor to avoid renal damage. It was reported that the prognosis of children with upper renal tract changes at birth did not seem to be any worse than children developing changes later in life [11] . Five of the 6 patients with renal scarring in Dik and al report, were started on therapy with intermittent catheterization and antimuscarinic therapy several months after birth [3] .…”
Section: Discussionmentioning
confidence: 96%
“…Early start of CIC is the most important factor to avoid renal damage. It was reported that the prognosis of children with upper renal tract changes at birth did not seem to be any worse than children developing changes later in life [11] . Five of the 6 patients with renal scarring in Dik and al report, were started on therapy with intermittent catheterization and antimuscarinic therapy several months after birth [3] .…”
Section: Discussionmentioning
confidence: 96%
“…However, up to 86% of children have normal kidneys at birth. 22 In the absence of effective bladder management, there is an increasing incidence of renal damage from 21% at 2 weeks and 28% by 3 months. 23 By the end of childhood, 30-60% have renal scars.…”
Section: Myelomenigocoelementioning
confidence: 99%
“…The problem is the neuropathic bladder, characterised by detrusor‐sphincter dyssynergia, which effectively causes functional bladder outflow obstruction (Figure 4). However, up to 86% of children have normal kidneys at birth 22 . In the absence of effective bladder management, there is an increasing incidence of renal damage from 21% at 2 weeks and 28% by 3 months 23 .…”
Section: Myelomenigocoelementioning
confidence: 99%
“…Inappropriate innervations of the urinary bladder can cause abnormal function during the storage and voiding phase, and in this way can also lead to renal damage/failure, with renal replacement therapy included [9,10]. Renal failure is still the most severe complication and remains the main cause of death both in adults and children with MMC since the late 1950s when shunting devices to treat the hydrocephalus were established [11,12]. The study by Muralikrishna et al [13] revealed that the median age for renal transplantation in MMC patients was 27 years.…”
Section: Introductionmentioning
confidence: 99%